Integrasi Login Tanpa Mengetik Password pada WordPress - Mochamad Arifin; Agus Bejo; Warsun Najib (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
Nowadays, almost everyone has an account on the internet, but some of them often use simple and guessable password, since a complex password is difficult to memorize. Surely, it will compromise the account security and system themselves. Therefore, an integrated login system without typing and remembering password is needed. This paper describes the development of an integrated login system that can perform authentication on a device without typing and remembering password by developing a WordPress plugin and a smartphone application. The development of the system has successfully shown the QR Code on the WordPress login page and automatically redirect the user to the admin page when the login process is done through scanning the QR code by using smartphone. Password only needs to be typed in the first login, and users do not have to retype it for the next login process. Android application development has resulted a password manager application that helps the users to manage the password and to have a secure password storage. Login integration without typing a password can improve account security and reduce the risk of man-in-the-middle and key-logger attack.